Menegosiasikan Aspirasi Global dan Keterikatan Lokal: Analisis Sosiologis tentang K-Pop, Ikatan Emosional, dan Performativitas Identitas Remaja di Ambon - Matayane, Gadrimon; Rahawarin, Yunus (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This study explores how adolescents in Ambon construct self-identity through the internalization of Korean popular culture (K-Pop) while maintaining ties to their local social context. Employing a qualitative approach—including participant observation, in-depth interviews, and digital ethnography—this research investigates how global aspirations, manifested through K-Pop fandom, changes in appearance, and participation in fan communities, are transformed into meaningful emotional and social expressions in everyday life. The findings reveal that youth identity performance is not passive imitation but a conscious negotiation of global cultural values with local religious, communal, and social norms. The study’s novelty lies in its geographic focus on Eastern Indonesia—an underrepresented site in popular culture studies—and its integration of affective sociology and youth cultural agency to frame glocalization as both an emotional and performative process. This research offers a significant contribution to cultural and emotional sociology by illuminating the active role of youth in reshaping identity through global media flows, while also providing conceptual grounding for more inclusive educational and cultural policy that reflects the complex dynamics of youth expression in a globalized era.